Administracyjnoprawny obowiązek szczepienia dzieci a zgoda przedstawiciela ustawowego na badania kwalifikacyjne - Haberko, Joanna (Studia Prawa Publicznego, 2019)
The article focuses on the analysis of the parent situation (or statutory representatives) who are under legal requirement to subject their children to preventive vaccination. The main deliberations focus on answering the question of how the parents’ (or statutory representatives’) position should be treated if they, relying on the principle of autonomy and their parental rights, and pointing to their duty to exercise care of a minor and to represent a minor child, fail to take any action intended to implement the obligation imposed by law. Parents refer to the principle of child’s welfare and argue that vaccination constitutes an essential threat to the values they recognise, such as autonomy, freedom to make decisions regarding the actual situation and legal position of a child, or the child’s welfare. The issue of parents’ autonomy and implementation of child’s welfare is raised. Parents often bring up an argument of the harmful eff ects of vaccination and claim that by refusing to agree to vaccination they exercise the principle of child’s welfare. The legal character of the refusal to consent to child vaccination is also analysed. Here, deliberations are set in the context of imprecisely formulated statutory provisions and their mutual relations, especially in the context of the meeting of acts from two branches of law: administrative and civil, and within the latter family law in particular. An attempt has been made to explain doubts whether despite the mandatory requirement and resulting from it obligation threatened with an administrative ﬁ ne statutory representatives still have a right to express or not consent for vaccination of their children or to decide about at any stage of the procedure.